Wine tourism and regional development - Correia, Ricardo (2018)
The characteristics of wine tourism make it absolutely compatible with the predominantly rural areas looking for sustainable development. One of the major problems associated with wine tourism, however, comes from the difficulty the wine-producing industry has in conceiving of tourism as a product likely to generate added value. Most wine producers still do not have a clear perception of the main principles of tourism, which would allow them to offer a quality product and understand the way this industry (so different from the wine industry) works. This fact makes it difficult to create an interlinked network between wine and tour- ism, and consequently to the wine tourism assertion. This chapter aims at obtaining greater insight into the relationship between wine tourism and regional develop- ment. For that an analysis was developed that puts in evidence the main reasons that may block the leverage of regional development through wine tourism. Wine routes are presented here as one of the most efficient ways to avoid these blockages.